The Effects of Taxes on the Performance of Smes in Nsuube Kauga Parish,Mukono TC Division - Victoria Nabukenya (Uganda Christian University, 2023)
The study sought toinvestigate the effects of taxes on the performance of SMEs in Nsuube-Kauga Parish, Mukono TC Division. The study was guided by three objectives: examining the relationship between tax rates and the performance of SMEs, establishing the relationship between tax incentives and the performance of SMEs and examining the relationship between tax compliance and the performance of SMEs in Nsuube-Kauga Parish, Mukono TC Division The study was carried out using explanatory research design where quantitative research approach was utilized. Stratified sampling method was used to get a sample of 80 respondents who were SME owners and managers of the selected businesses dealing in segmented businesses and assorted merchandize in Kauga village, Nsuube-Kauga Parish, Mukono TC Divisionand these responded to the questionnaires that were used to collect data. From the study findings, it was revealed thattax policies play a crucial role in shaping SMEs’ growth and viability. The high agreement among respondents on the clarity of tax rates and the awareness of SMEs regarding tax payment procedures is promising. However, the study also highlights significant concerns, with many SME owners perceiving taxes as burdensome, especially due to their regressive nature, which negatively affects revenue bases. Furthermore, the lack of perceived tax incentives for SMEs hinders their potential for growth and expansion in the area. In conclusion, the study highlights the importance of tax compliance for SMEs' success. SME owners who consistently file returns, pay taxes on time, and adhere to tax regulations demonstrate a positive correlation with improved SME performance. Finally, the study proposed a comprehensive set of recommendations to bolster the growth and ease the tax burden on small and medium-sized enterprises (SMEs). These include simplifying tax policies, introducing targeted tax incentives, enhancing tax education programs, reforming regressive tax measures, fostering collaboration between tax authorities and SMEs, conducting regular policy evaluations, and establishing a dedicated tax ombudsman for SMEs. By streamlining taxes, providing incentives, educating SMEs, and promoting cooperation, policymakers can create a supportive environment that encourages SME growth, innovation, and compliance while addressing their unique challenges.
This is a dissertation.